Metrorail : building on the success of 2010 - Metton, Eulalie; Mosala, Thabo ([London] : SAGE, 2016)
It was June 2011 and South African passenger rail company, Metrorail, was celebrating its success in moving passengers during the 2010 FIFA World Cup. The organisation had done much to improve its infrastructure, safety and image for the event. Now Lucky Montana, group chief executive officer (CEO) of the Passenger Rail Agency of South Africa (PRASA) - the state-owned enterprise that owned Metrorail - considered what the organisation should do to ensure that Metrorail become the preferred, regular transport service for thousands of daily commuters still using taxis or their own cars.
Originally Published in: Metton, E., & Mosala, T. (2013). Metrorail: Building on the Success of 2010. WBS-2013-24. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Metrorail (South Africa : Firm); Corporate turnarounds -- Case studies; Consumer behavior -- Case studies